1994
DOI: 10.2105/ajph.84.7.1106
|View full text |Cite
|
Sign up to set email alerts
|

Work-related traumatic brain injury in Washington State, 1988 through 1990.

Abstract: OBJECTIVES. Brain trauma is a major cause of disability in the United States, especially among young adults. Work-related brain trauma cases represent a subpopulation that may be amenable to intervention efforts, but largely because of unavailability of data, this group has not previously been studied. METHODS. Washington State workers' compensation data were used to identify brain trauma cases and to describe incidence rates with respect to age, gender, and industrial classification. Cause of injury was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 11 publications
7
14
2
Order By: Relevance
“…The accident event/ exposure pattern is similar to those reported earlier (Cohen et al, 1999;Heyer & Franklin, 1994). Falls from elevation were the most frequent exposure/event at 39%.…”
Section: External Causes Of Injury Exposures and High Risk Occupationssupporting
confidence: 88%
See 2 more Smart Citations
“…The accident event/ exposure pattern is similar to those reported earlier (Cohen et al, 1999;Heyer & Franklin, 1994). Falls from elevation were the most frequent exposure/event at 39%.…”
Section: External Causes Of Injury Exposures and High Risk Occupationssupporting
confidence: 88%
“…The results, shown in Table 4, confirmed the existence of previously identified predominant patterns in logging, trucking, roofing, and building construction (Heyer & Franklin, 1994). A new cluster involving motor-vehicle accidents among sales workers/managers was also identified.…”
Section: Hazard Analysis Cluster Analysis and Injury Descriptionssupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies have been limited in that they have only been able to characterize the severity of head injuries for falls in general, such as by hospital length of stay [5] or injury severity score [4], whereas in this study it was found that those who sustained a FFE were more likely to sustain multiple injuries (e.g. upper and/or lower limb fractures/injuries, head/neck injuries, spinal injuries) including at least a head injury compared to those who FFSL.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic brain injuries are often associated with a slow recovery pattern [2] and significant claim costs [3]. Falls are a major cause of work-related TBI [4][5][6][7] and death [8][9][10]. Although the construction industry is a high-risk population for serious TBI due to falls [4-6, 9, 11], there have been few studies that have characterized workers who experienced a fall and the nature of injuries due to falls in detail such as differentiating between falls from the same level and falls from an elevation [12].…”
Section: Introductionmentioning
confidence: 99%